Pengaruh Jalan Santai Terhadap Perubahan Kadar Glukosa Darah Pada Pra Lansia Desa Temon Boyolali - Saputri, Dian Mahfudz Asri; , dr. Sigit Widyatmoko, Sp. PD, M. Kes; , dr. Safari Wahyu Jatmiko (2015)
Background Physical inactivity is the fourth important risk factor in the world that cause 3,2 milion people dying. 21-25% people get breast dan colon cancer, 27% get diabetes, and 30% get heart disease related to their physical inactivity. 26,1 % people in indonesia and 20,5% in central java are insufficient from doing physical activity. Walking is promoted as popular aerobic moderate intensity of physical activity in daily life. People do not need skill, expensive equipment, cloth, special facilities, patner, spesific age. Walking have less risk of muskuloskeletal injury. This study aimed to investigate the influence of slow walking to blood glucose level changes in middle age. Methods Observational analitic crossectional design with purposive sampling. Three days before blood glucose measured 58 participant sugested for eat as usual and one day before participants fasting for 8 hours but allowed for drink water. They eat 50 gram boiled corn. Two hours later blood glucose level measured. They walk 2520 m long. They suggest for walk in 0,4-1,4 metres per second. After walk their blood glucose level measured again. Results There is weak correlation (r=0,20-0,399) and not significant( p>0,05) influence between slow walking and blood glucose level. Conclution There is no influence of slow walking to blood glucose level changes in middle older healthy population in Temon Boyolali.